Dog and cat bite wounds - epidemiological characteristics, forensic investigation and civil liability - Marjanski, Vladimir; Поткоњак, Александар (Zbornik radova Pravnog fakulteta u Novom Sadu, 2016)
People injuries after bites of a dog and/or cat are contemporary and all the time issue. The consequences that stem out of this relationship of people and dogs and/or cats are numerous - medical, utility-environmental, sociological, legal and economic. The subject of this paper is to analyze the epidemiological characteristics of wounds caused by dog and cat bites, their forensic examination and analysis of civil liability of subjects/entities responsible for damages resulting from bite of dogs and cats. Forensic examination is carried out by reconstruction of events, identification of the dog/cat, determination of pathological condition in the dog/cat and the injured party and the estimatimation of  alternative explanations. Within the analysis of civil liability, legal basis of liability, the persons responsible for compensation, types of damages and reasons for the disclaimer are determined.